A Comprehensive Description of Multi-Term LSM for Applying Multiple a Priori Constraints in Problems of Atmospheric Remote Sensing: GRASP Algorithm, Concept, and Applications - Dubovik, Oleg; Fuertes, David; Litvinov, Pavel; Lopatin, Anton; Lapyonok, Tatyana; Doubovik, Ivan; Xu, Feng; Ducos, Fabrice; Chen, Cheng; Torres, Benjamin; Derimian, Yevgeny; Li, Lei; et al. (Frontiers in Remote Sensing, 2021)
Advanced inversion Multi-term approach utilizing multiple a priori constraints is proposed. The approach is used as a base for the first unified algorithm GRASP that is applicable to diverse remote sensing observations and retrieving a variety of atmospheric properties. The utilization of GRASP for diverse remote sensing observations is demonstrated.